EKSISTENSI MAHASISWA MELALUI PEMBERDAYAAN BIDANG KEAGAMAAN DI NAGARI SIMANAU - irwandi irwandi (KOMUNITAS, 2022)
Abstract: Student involvement in religious activities is a must for students, especially students of the Department of Islamic Community Development (PMI) of the Faculty of Ushuluddin, Adab and Da'wah IAIN Batusangkar. This direct involvement is one form of applying science, especially in scientific studies of community development. Community service activities carried out by PMI students who are under the auspices of the PMI majors student association and their lecturers are carried out for one week located in Nagari Simanau Kab. solo. The research carried out in this activity is to see the extent to which students exist using a qualitative method with a descriptive approach. From the results of the research, it was found that the involvement of students in community service activities is very much needed because this involvement has a positive impact on the program and the actualization of activities in the future. Keywords: student; da'wah; devotion